Religious Orientation and its Relationship to Meaning of Life and Irrational Thinking among a Sample of University Student in Jeddah - Nouf G. Arfashah (Sultan Qaboos University, 2018)
The study aimed at exploring the relationship between religious orientation and the meaning of life on one hand, and religious orientations and irrational thinking on the other hand. It also aimed at exploring the relationship between the meaning of life and irrational thinking. The basic sample comprised 585 participants from university students in Jeddah, who were randomly selected from various humanities, religion and science majors. Research instruments included a religious orientation scale, meaning of life scale, and thoughts and beliefs scale. The study found: (1) a positive correlation between meaning of life and each of the intellectual cognitive religiousness, emotional enthusiastic religiousness and original true religiousness; (2) a negative correlation between meaning of life and ritual opportunist religiousness;  (3) a positive correlation between irrational thinking and and each of the intellectual cognitive religiousness, ritual opportunist religiousness and emotional enthusiastic religiousness; and (4) a negative correlation between the meaning of life and the inflexibility of thinking which is one aspect of irrational thinking.